1998
DOI: 10.1136/bmj.316.7145.1643
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serious eye disease and visual impairment in a north London population: population based, cross sectional study

Abstract: Objective: To estimate the magnitude of serious eye disorders and of visual impairment in a defined elderly population of a typical metropolitan area in England, and to assess the frequency they were in touch with, or known to, the eye care services. Design: Cross sectional survey using two stage cluster random sampling. Setting: General practices in north London. Subjects: Random sample of people aged 65 and older, drawn from a defined population of elderly people registered with 17 general practice groups. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
208
3
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(220 citation statements)
references
References 8 publications
7
208
3
2
Order By: Relevance
“…In the UK since the early 1980s there have been four cross-sectional surveys of eye disease [2][3][4][5] and two that have dealt with minority groups. 9,10 Uniquely the Speedwell Eye study examined a group of men who have been part of a prospective study of heart disease and stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK since the early 1980s there have been four cross-sectional surveys of eye disease [2][3][4][5] and two that have dealt with minority groups. 9,10 Uniquely the Speedwell Eye study examined a group of men who have been part of a prospective study of heart disease and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…1 Surveys reporting the prevalence of cataract in the UK have been undertaken previously. [2][3][4][5] The Framingham study in the US has reported data from a cohort followed for cardiovascular disease, 6 but no similar studies in the UK have examined such a group.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported associations between lower socio economic status and cataract.2 4 ,2 5 Reidy et al 6 found the age-standardised prevalence of poor vision to be significantly higher in underprivileged areas (identified by Jarman scores) in north London. The main contributory disorders were refractive errors and cataract.…”
Section: Other Studiesmentioning
confidence: 99%
“…[1][2][3][4][5] Epidemiological studies reveal that between 12 and 30% of persons aged 75 years and older in the United Kingdom have impaired vision [6][7][8] and in many cases these patients are not in contact with either the hospital or community eye services. 8,9 These data suggest that a significant number of patients who sustain a fractured neck of femur after a fall will therefore have impaired vision. They also suggest that in many patients the fall may have been a direct consequence of this visual impairment and furthermore the patient themselves may be unaware of this disability.…”
Section: Introductionmentioning
confidence: 99%